Incisional hernia rates after laparoscopic or open abdominal surgery—a systematic review and meta-analysis - Kössler-Ebs, Julia; Grummich, Kathrin; Jensen, Katrin; Hüttner, Felix; Müller, Beat P.; Seiler, Christoph M.; Knebel, Phillip; Büchler, Markus W.; Diener, Markus K. (World journal of surgery, 2016)
Incisional hernias are one of the most common long-term complications associated with open abdominal surgery. The aim of this review and meta-analysis was to systematically assess laparoscopic versus open abdominal surgery as a general surgical strategy in all available indications in terms of incisional hernia occurrence.
Gesehen am 22.05.2020